ANALISA PRODUKTIFITAS MESIN PENCACAH BIJI JAGUNG MENJADIJAGUNG HALUS DENGAN MODEL PISAU ROTARI KAPASITAS 60 KG/ JAM - Sigalingging, Rihard Tua; Sutrisno, Franky (MEKANIK: Jurnal Ilmiah Teknik Mesin, 2019)
The corn seed counting machine is a machine used to process corn kernels into fine corn. The working principle of the corn seed chopping machine is driven by an electro motor which is connected through a pulley strap to the engine drive shaft. The process of counting fine corn, corn seeds is collected in a container. Turn on the engine a few moments before the test is done, then the corn kernels are poured into the machine shelter. In testing the productivity performance of the corn seed chopping machine using a rotary knife model. For the engine analyzed initially a capacity of 60 kg / hour. After the results of testing the engine productivity, which is obtained at the first test 121.06 kg / hour and the second test 115.05 kg / hour obtained from the total capacity. While the power required in the first experiment was 7.83 watts and the second experiment was 7.33 watts obtained from the load loss which was reduced by electro motor losses